Gerakan Moral dan Religiusitas Digital: Kajian Budaya atas Aktivisme Keagamaan Online Akun Instagram Project Dakwah di Makassar - hadi saputra (JOISCOM (Journal of Islamic Communication), 2026)
Employing a descriptive qualitative approach grounded in cultural studies, the research treats Instagram as a cultural space in which meaning is produced. Data were collected through digital observation of circulating post traces, documentation of posters and captions, and analysis of audience interaction patterns across public channels connected to Project Dakwah.The findings indicate that Project Dakwah constructs a consistent pattern of poster-based moral messaging that emphasizes self-reflection, emotional intimacy, and everyday piety. Message compression and minimalist visual design render da‘wah compatible with the logics of visibility and circulation characteristic of social media platforms. At the same time, the study identifies a conversion mechanism through which online resonance is translated into offline action via operational pathways of participation, including donations, scheduled almsgiving, Qur’an classes, study circles, volunteering, and the strengthening of offline da‘wah spaces. The study concludes that Project Dakwah’s digital da‘wah exhibits the ambivalence of the mediatization of religion, simultaneously expanding reach while compressing meaning, yet sustained by community-deepening strategies that support the continuity of social practice. Keywords: digital da‘wah; Islamic Instagram; digital religiosity